Extreme obesity in the intensive care unit - Joseph Varon; Najia Hussaini (Indonesian Nutrition Association, 2023)
Morbid obesity is a highly serious condition that significantly impairs health worldwide. This is especially prominent during the COVID-19 pandemic, as lockdowns and reduced physical activity contributed to the problem. Overweight and obese adults are at a higher risk of various acute and chronic medical conditions, including hypertension, heart disease, diabetes, respiratory problems, certain cancers, gout, and arthritis. While some individuals may have higher muscle or bone mass accounting for excess weight, the majority of those exceeding 20% of their ideal body weight have excessive fat. Disturbingly, obesity rates in the USA have been progressively increasing since the first survey conducted in 1960. Recent data shows that obesity prevalence in the USA is three times higher than in France and one-and-a-half times higher than in England. Given the widespread nature of obesity and its association with numerous diseases, it is not surprising that many obese patients require treatment in the intensive care unit (ICU).